SNX3 mediates heart failure by interacting with HMGB1 and subsequently facilitating its nuclear-cytoplasmic translocation - Li Hong; Peng Ming-xia; Yang Rui-xue; Chen Jian-xing; Wang Yue-mei; Wang Pan-xia; Hu Yue-huai; Pan Di-yi; Liu Pei-qing; Lu Jing (Acta Pharmacologica Sinica, 2025)
Sorting nexins (SNXs) as the key regulators of sorting cargo proteins are involved in diverse diseases. SNXs can form the specific reverse vesicle transport complex (SNXs-retromer) with vacuolar protein sortings (VPSs) to sort and modulate recovery and degradation of cargo proteins. Our previous study has shown that SNX3-retromer promotes both STAT3 activation and nuclear translocation in cardiomyocytes, suggesting that SNX3 might be a critical regulator in the heart. In this study we investigated the role of SNX3 in the development of pathological cardiac hypertrophy and heart failure. We generated abdominal aortic constriction (AAC) rat model and transverse aortic constriction (TAC) mouse model; hypertrophic neonatal rat cardiomyocytes (NRCMs) were induced by exposure to isoproterenol (10 μM). We showed that the expression of SNX3 was significantly upregulated in ISO-treated NRCMs and in the failing heart of AAC rats. Overexpression of SNX3 by intramyocardial injection of Ad-SNX3 induced heart failure in rats, and increased the susceptibility of NRCMs to ISO-induced myocardial injury in vitro. In contrast, conditional knockout of SNX3 in cardiac tissue in mice rescued the detrimental heart function in TAC mice, and knockdown of SNX3 protected against ISO-induced injury in NRCMs and AAC rats. We then conducted immunoprecipitation-based mass spectrometry and localized surface plasmon resonance, and demonstrated a direct interaction between SNX3-retromer and high mobility group box 1 (HMGB1), which mediated the efflux of nuclear HMGB1. Moreover, overexpression of HMGB1 in NRCMs inhibited the pro-hypertrophic effects of SNX3, whereas knockdown of HMGB1 abolished the protective effect of SNX3-deficiency. These results suggest that HMGB1 might be a direct cargo protein of SNX3-retromer, and its interaction with SNX3 promotes its efflux from the nucleus, leading to the pathological development of heart failure.